Handling default risks in microfinance: the case of Bangladesh - Kassim, Salina; Rahman, Mahfuzur (Emerald Group Publishing Ltd., 2018)
Purpose – This paper aims to identify incidences of default risks in microfinance. Design/methodology/approach – Semi-structured interviews were conducted with individual borrowers in Grameen Bank. Upon completing the interview session from 40 respondents, the results of the interviews are interpreted by a comprehensive content analysis. Findings – This study identifies the incidences of defaults in microfinance, which are post-disbursement monitoring, technical assistance, inexperienced field workers, weekly payment, accessible database, family member illness, hiding business, lack of motivation and over-stretched financial commitments. Among these incidences, the findings indicate that post-disbursement supervision is highly relevant in ensuring the success of microfinance because 80 per cent of the recipients of microfinance are illiterate women. Originality/value – This study would be helpful for the investment companies, financial institutions, creditors and borrowers of microfinance. The financial institutions and investment companies need to identify borrower capacity and any obligation that may impede with repayment. It may help them to maximize returns on profit and minimize the risk of losses which contribute to economic growth.